The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/1078155220985579
|View full text |Cite
|
Sign up to set email alerts
|

Exploring practice site contributions and professionalization impact of engaging student pharmacists on hematology-oncology advanced pharmacy practice experience rotations

Abstract: Introduction Student pharmacists contribute meaningfully to patient care during Advanced Practice Pharmacy Experiences (APPEs) in varied settings. We aimed to characterize and evaluate the impact of student participation in hematology-oncology (hem-onc) APPEs on the practice site, and on student professionalization. Methods For students completing hem-onc APPEs during 2016–2019, rotation activities and post-APPE self-reflections describing meaningful impact were reviewed; activities were categorized into direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Three of these dimensions (F1, F2 and F4) correspond to the cognitive, cultural, and identity-related learning identified by Abrandt Dahlgren et al (2006) and Reid et al (2011), who qualitatively and longitudinally studied identity formation in students from three professional fields through their developmental trajectory from the university context to the workplace. Qualitative research on the professionalization of university students has shown that socio-professional experiences influence professionalism and ethics (Briceland et al, 2020), that clinical placements influence the development of practical, communication and collaboration competencies (Yacobucci et al, 2022), and that the learning contract influences the development of competencies. While other research (qualitative, quantitative and mixed) has focused on the effects of training programs, either on competency development and labor market readiness (Prince et al, 2005;Schmidt et al, 2009;Vaatstra & de Vries, 2007) or on the construction of a professional identity (Björkström et al, 2008;Dannels, 2000;Dryburgh, 1999;Du, 2006), only our earlier studies (Bélisle, 2011;Bélisle et al, 2021) covered all the dimensions associated with the professionalization of university students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of these dimensions (F1, F2 and F4) correspond to the cognitive, cultural, and identity-related learning identified by Abrandt Dahlgren et al (2006) and Reid et al (2011), who qualitatively and longitudinally studied identity formation in students from three professional fields through their developmental trajectory from the university context to the workplace. Qualitative research on the professionalization of university students has shown that socio-professional experiences influence professionalism and ethics (Briceland et al, 2020), that clinical placements influence the development of practical, communication and collaboration competencies (Yacobucci et al, 2022), and that the learning contract influences the development of competencies. While other research (qualitative, quantitative and mixed) has focused on the effects of training programs, either on competency development and labor market readiness (Prince et al, 2005;Schmidt et al, 2009;Vaatstra & de Vries, 2007) or on the construction of a professional identity (Björkström et al, 2008;Dannels, 2000;Dryburgh, 1999;Du, 2006), only our earlier studies (Bélisle, 2011;Bélisle et al, 2021) covered all the dimensions associated with the professionalization of university students.…”
Section: Discussionmentioning
confidence: 99%
“…Although some research has focused on the effects of training modalities on the professionalization of healthcare students (Björkström et al, 2008;Briceland et al, 2020;Jubin, 2013;Yacobucci et al, 2022), empirical studies on the professionalization of individuals in a university context are still few and far between (Abrandt Dahlgren et al, 2006;Bélisle, 2011), and the very concept of professionalization is rarely defined. Three dimensions of professionalization seem to recur: 1) the development of professional competencies, 2) the appropriation of the professional culture and 3) the construction of a professional identity.…”
Section: Introductionmentioning
confidence: 99%